2009
DOI: 10.1002/stem.268
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin Signaling Increases in Proliferating NG2+ Progenitors and Astrocytes during Post-Traumatic Gliogenesis in the Adult Brain

Abstract: Wnt/β-catenin signaling can influence the proliferation and differentiation of progenitor populations in the hippocampus and subventricular zone, known germinal centers in the adult mouse brain. It is not known whether β-catenin signaling occurs in quiescent glial progenitors in cortex or spinal cord, nor is it known whether β-catenin is involved in the activation of glial progenitor populations after injury. Using a β-catenin reporter mouse (BATGAL mouse), we show that β-catenin signaling occurs in NG2 chondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 52 publications
(85 reference statements)
5
76
0
Order By: Relevance
“…20 Specific changes to the mechanics of the device include an update to the injury probe linkage to include a Lucite platform that is threaded directly in line with the injury probe. This provides a more rigid reference point for the noncontacting position sensor (KD-2306; Kaman Precision Products, Colorado Springs, CO), and allows for rapid modification of the reference gap when injury displacement calibration is modified between mice and rats.…”
Section: Updated Electromagnetic Spinal Cord Injury Devicementioning
confidence: 99%
“…20 Specific changes to the mechanics of the device include an update to the injury probe linkage to include a Lucite platform that is threaded directly in line with the injury probe. This provides a more rigid reference point for the noncontacting position sensor (KD-2306; Kaman Precision Products, Colorado Springs, CO), and allows for rapid modification of the reference gap when injury displacement calibration is modified between mice and rats.…”
Section: Updated Electromagnetic Spinal Cord Injury Devicementioning
confidence: 99%
“…The NG2 cells are widely and abundantly present in the adult brain (Dawson et al, 2000) and can give rise to oligodendrocytes and neurons, but not to astrocytes under the same physiological conditions (Dawson et al, 2003;Dayer et al, 2005;Tamura et al, 2007a). On the other hand, the NG2 cells were reported to generate astrocytes during perinatal development (Zhu et al, 2008;Guo et al, 2009) and in the adult brain and spinal cord which underwent acute injury with neuronal death or gliosis (Hampton et al, 2004;Magnus et al, 2007;Zhao et al, 2009;White et al, 2010). Based on these findings, we investigate here whether astrogenesis occurs in the cerebral cortex following cortical SD, which is a potent stimulus for NG2 cell proliferation without cell death.…”
Section: Introductionmentioning
confidence: 99%
“…28 In agreement, SCI has been reported to not promote Wnt canonical activation in BATgal transgenic mice. 32 However, new recent experimental evidences are providing contradictory data in support of Wnt expression, with key roles in both the healthy and damaged spinal cord of adult mice. In this line of research, a recent wide screening in the spinal cord of adult mice has shown a constitutive expression of most Wnt family members, as well as the expression of several Wnt ligands (Wnt1, Wnt3a, Wnt4, and Wnt5a), receptors (Fz1 and Fz2), b-catenin, and, remarkably, Wnt inhibitory factor 1 (Wif1) by neurons and astrocytes as a result of amyotrophic lateral sclerosis progression.…”
mentioning
confidence: 99%